2018
DOI: 10.1161/str.49.suppl_1.wp48
|View full text |Cite
|
Sign up to set email alerts
|

Abstract WP48: Computed Tomography Perfusion Core Infarct Measurement Compared to Diffusion-Weighted Magnetic Resonance Imaging in Patients With Revascularization of Anterior Circulation, Large Artery Occlusions

Abstract: Introduction: Automated CT Perfusion (CTP) technology offers the potential to distinguish irreversibly damaged tissue from “at-risk,” potentially salvageable tissue. Regional Cerebral Blood Flow (CBF) < 30% has been identified as a good predictor of infarct core on CTP. Randomized trials investigating mechanical thrombectomy for large artery occlusion (LAO) acute ischemic stroke (AIS) have excluded patients with large core infarcts. We investigated the relationship between infarct core, as predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A search of the references of included studies and previous systematic reviews [17, 18, 20, 21] identified 4 additional studies. A total of 167 full-text papers were reviewed and 48 studies [8, 12‒14, 29‒72] met the inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…A search of the references of included studies and previous systematic reviews [17, 18, 20, 21] identified 4 additional studies. A total of 167 full-text papers were reviewed and 48 studies [8, 12‒14, 29‒72] met the inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%